Brief fear preexposure facilitates subsequent fear conditioning. (June 2015) - Iwasaki, Satoshi; Sakaguchi, Tetsuya; Ikegaya, Yuji
Highlights: A preceding foot shock enhances subsequent fear conditioning. The effect of the preceding shock lasts for at least 7 days. It was inhibited by an NMDA receptor antagonist. Abstract: Post-traumatic stress disorder (PTSD) is an anxiety disorder that occurs following an unexpected exposure to a severe psychological event. A history of a brief trauma is reported to affect a risk for future PTSD development; however, little is known about the mechanisms by which a previous trauma exposure drives the sensitivity to a late-coming trauma. Using a mouse PTSD model, we found that a prior foot shock enhances contextual fear conditioning. This shock-induced facilitation of fear conditioning ( i.e., priming effect) persisted for 7 days and was prevented by MK801, an N -methyl-d -aspartate receptor antagonist. Other types of trauma, such as forced swimming or tail pinch, did not induce a priming effect on fear conditioning. Thus, a trauma is unlikely generalized to modify the sensitivity to other traumatic experiences. The behavioral procedure employed in this study may be a useful tool to elucidate the etiology of PTSD.